The Administrative Judiciary’s Reform in Kazakhstan - Shajachmetova, Aiym (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The study concerns the reform of administrative judiciary in Kazakhstan, consisting in the organizational separation of administrative courts and shaping them as a system of courts with a three-tier structure. This change was accompanied by the codification of administrative court proceedings, which – unlike the method of legal regulation in European legal orders – consisted in regulating administrative court proceedings together with administrative proceedings in one legal act: the Code of Administrative Procedure of June 29, 2020 (effective from July 1, 2021). The characteristic features of Kazakh administrative court proceedings are the court’s efforts to resolve the matter as quickly as possible. To this end, the principle of an active role of the court was established with its broad obligations as regards the taking of evidence and judicial review of the execution of a judgment by an administrative authority. Within the court-administrative procedure, there are visible inspirations from the German act on administrative judiciary. This applies in particular to types of complaints and methods of amicable settlement of a court dispute. Due to the fact that the rules of judicial control of the administration were only developing in Kazakhstan, the court was equipped with far-reaching coercive measures. The presented analysis leads to the conclusion that the Kazakh code corresponds to the procedural standards established in Europe and it will certainly contribute to the consolidation of the rule of law in the Kazakh legal system which has only recently developed in this direction.